MECHANICAL PROPERTIES AND PERFORMANCE EVALUATION OF RECYCLED POLYPROPYLENE AND TREATED MENGKUANG LEAVES COMPOSITES - Che Aslan, Nasrul Haziq (IRC, 2017)
Due to environmental friendly, light weight, low cost, renewability and adequate mechanical properties, natural fiber composite is preferred in many applications such as automotive, aerospace, civil and sports. Locally, mengkuang leaves (ML) has great potential to be used as reinforcement. However, there is limited effort to study the performance of ML especially with recycled polypropylene (r-PP). Therefore, this experiment is to study the mechanical properties of r-PP reinforced ML composite. Combination of two individual materials are facing incompatibility to have better mechanical properties due to its interfacial bonding. The aim of this study is to evaluate the effects of sodium hydroxide (NaOH) and maleic anhydride-grafted polypropylene (MAPP) on mechanical properties of r-PP/ML composite. The composite was compounded by 60 wt.% of r-PP and 40 wt.% of ML by twin screw extruder and injection molding process was used to fabricate the composite test specimens. To study the effect of NaOH and MAPP, ML was treated with 5% concentration of NaOH for a day and 5 wt.% of MAPP was added into the composite. Tensile, flexural and impact properties of the composite were determined according to their respective ASTM standards. Tensile and flexural properties generally showed improvements compared to neat r-PP. However, an adverse effect was observed in the impact strength. This result was expected due to the nature of short fiber employed which would decrease impact property compared to neat r-PP. The highest tensile strength was observed on r-PP/TML/MAPP composite with an improvement of 27.8%. The results also indicated that MAPP dominantly improved tensile and flexural strength while NaOH treatment dominantly contributed to improvement in tensile and flexural moduli.